Resting Tremor after Mild Head Injury: Case Report - Magalhães, Marcelo José da Silva de; Martins, Ana Paula Alkmim Figueiredo; Freire, Anna Freitas Cardoso; Dias, Jamile Pereira; Ribeiro, Ludmila Godinho; de Oliveira, Mariana Alves; Mendes, Mateus Oliveira; de Carvalho, Monique Rocha; Versiani, Theresa Cristina Abreu (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Over the past few decades, it has been recognized that traumatic brain injury (TBI) may result in various movement disorders. However, moderate or mild TBI only rarely causes persistent post-traumatic movement disorders. In the present report, we describe a case of secondary tremor due to a mild head injury with a transitory loss of consciousness. A 26-year-old man developed an isolated rest tremor of the hands and legs without other neurologic signs. The interval between the head trauma and the onset of the symptoms was 4 months. Neuroimaging studies reveled gliosis in the lentiform nucleus. Haloperidol administration resulted in tremor reduction. A rest tremor, similar to essential tremor, can be a rare complication of head trauma. Haloperidol may be an effective and safe treatment modality for post-traumatic tremor. Further studies are needed to clarify the optimal drug for the treatment of post-traumatic tremor.
Keywords: traumatic brain injury; movement disorder; posttraumatic; tremor